Defences in unjust enrichment - Dyson, Andrew; Goudkamp, James, 1980-; Wilmot-Smith, Frederick, 1986- (Hart studies in private law. Essays on defences, 2016)
This book is the second in a series of essay collections on defences in private law. It addresses defences to liability arising in unjust enrichment. The essays are written from a range of perspectives and methodologies. Some are doctrinal, others are theoretical, and several offer comparative insights. The most important defence in this area of the law, change of position, is addressed in detail, but many other defences are treated too, as well as the interrelations between these defences within the law of unjust enrichment. The essays offer novel claims and ways of looking at problems in this challenging area of legal study.